(untitled) (Research, Society and Development, 2022)
Excess maternal weight is a risk factor for gestational diabetes, increased blood pressure, circulatory problems, and an increase in cesarean deliveries. Objective: to evaluate the prevalence of overweight among Brazilian pregnant women and the clinical and nutritional repercussions for the mother and child. Methods: bibliographic review, of an integrative nature. Original articles, abstracts and full texts were used, available for analysis, that addressed the topic; articles published in Portuguese and English. After analyzing all the articles and applying the inclusion criteria, 12 articles were selected for the elaboration of the work. Results: In the analyzed studies, the prevalence of overweight among Brazilian pregnant women was evidenced; it was observed that pregnant women who were classified as overweight and obese at the beginning of prenatal care had inadequate weight progression until the end of pregnancy, being associated with the presence of metabolic comorbidities and hypertensive syndrome; as for the newborn, it was observed that the probability of having a large baby for its age is 1.4 to 3.5 times greater in overweight pregnant women. Conclusion: Although adequate weight gain is recommended during pregnancy, it is common for women to gain more weight than recommended, with the need to integrate health actions related to the promotion of healthier eating habits in prenatal care to prevent outcomes. adverse effects of excess weight gain during pregnancy and prevent negative implications for the health of the mother and child.